Supply Chain Management Model at Pumpkin Production Center in East Java - Haryono, Haryono; Siswati, Endhang; Epriliati, Indah; Muchid, Mochammad; Salmon, Indra Pratama Putra (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
This study is based on the need to make pumpkin as an alternative in food diversification through the role of business people. The initial strategy was to approach mapping the actors in the pumpkin agriculture sector from upstream to downstream. The aim of this research was to map the supply chain management of pumpkin in pumpkin production centers in East Java. This research used qualitative methods and participatory approaches. Data collection was done through in-depth interviews, observation, and study of documents and data. The results showed that the management of pumpkin supply chain in East Java had a structure, mechanism, and institutional pattern. The existing structure was formed through the role of 9 (nine) business operators in the pumpkin agriculture sector. Information flow occurs in two directions in the form of information on the quality and quantity of pumpkin harvested, the market price of pumpkin, previous collaboration experience, products that have been produced from pumpkin, pumpkin distribution schedule, and product innovations that have been produced from pumpkin harvest. Financial flow was carried out in the form of cash and credit between business actors. The product flow is in the form of fresh pumpkin products to semi-processed products such as pumpkin chips and pumpkin flour. Based on the supply chain flow patterns, the interwoven relationships that occur are vertical/horizontal as well as trade and partnership patterns.